Socioemotional wealth: A systematic literature review from a family business perspective - Felipe Hernández-Perlines; Luis Araya-Castillo; Cristian Millán-Toledo; Manuel Alejandro Ibarra Cisneros (European Research on Management and Business Economics (ERMBE), 2023)
The purpose of this study is to conduct a bibliometric analysis of socioemotional wealth research from the perspective of the family business. This analysis describes the current research trends and shows the future lines of research to guide future research in this field. A detailed and systematic analysis of the scientific production of 1026 articles on socioemotional wealth published in the Web of Science (WoS) between 1975 to May 2021. This work shows the consolidation of socioemotional wealth as an area of research in family business, whose development has occurred since 2007. On the other hand, the most important articles, authors, countries and institutions in research on socioemotional wealth are pointed out. Finally, this paper concludes that the theoretical foundation of socioemotional wealth as an area of research is due to its connection with Family Business Theory.
Keywords: C88; D21; M21; 650; Socioemotional wealth; Family firm; Bibliometric analysis; VOSviewer